Mixed Programming Realization of the EMD-WVD Combined Method - Miaozhong Sun; Hongtao Tang; Yuanli Xu (Institute of Advanced Engineering and Science, 2013)
Winger-Ville Distribution (WVD) possesses high time-frequency concentration and resolutions, but brings serious cross-terms in process of a multi-component signal to distort greatly the result of time-frequency analysis. Because of this the use of the WVD is limited for many applications. In this paper a combined method is proposed: Empirical Mode Decomposition (EMD) is first used to decompose the original signal into a series of Intrinsic Mode Functions (IMFs), then false IMFs among them are eliminated according to the correlation coefficients between each IMF and the original signal, WVD is utilized to analyze the remanent IMFs, finally each WVD is added linearly with together to reconstruct the whole WVDs of the original signal. In order to carry out and validate the combined method, a time-frequency analytic system is designed and realized by using MATLAB and Delphi mixed programming based on COM (Component Object Model) module technology. This system is used to perform vibration signal time-frequency analysis of a grinding machine. The analytic results show validity of the combinedl method and success of the mixed programming. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2360